Leafy vegetables inhibit activities of aldose reductase and sorbitol dehydrogenase in vitro. Issue 6 (2nd November 2021) - Kazeem, Mutiu Idowu; Umukoro, Oghenemaro Glory; Ogunrinola, Olabisi Olufunmilayo; Nafiu, Mikhail Olugbemiro; Akanji, Musbau Adewunmi
ABSTRACT: One of the processes involved in pathogenesis of diabetic complications is the polyol pathway, which is catalyzed by the enzymes – aldose reductase and sorbitol dehydrogenase. Inhibition of one, or both, of these enzymes will shut down the polyol pathway ameliorating diabetic complications. Consumption of leafy vegetables is a dietary regime for management of diabetes mellitus and its complications. Inhibitory effects of leafy vegetables on activities of the polyol pathway enzymes aldose reductase and sorbitol dehydrogenase, and mode(s) of inhibition of these enzymes by the most effective plant were evaluated. Aqueous extract of leaves of African eggplant ( Solanum macrocarpon L), bitter leaf ( Vernonia amygdalina Del.), fluted pumpkin ( Telfairia occidentalis Hook.) and clove basil leaf ( Ocimum gratissimum L), were incubated with substrates (glucose and sorbitol) and enzymes, and their percent inhibition of enzymes determined spectrophotometrically. Due to low IC50 value, the aqueous extract of bitter leaf was used to assess kinetics of both enzymes. With exception of African eggplant, all plants displayed stronger inhibition of sorbitol dehydrogenase than aldose reductase. Vernonia amygdalina exhibited the lowest IC50 for aldose reductase (78.03 µg∙mL −1 ) and sorbitol dehydrogenase (22.17 µg∙mL −1 ). Vernonia amygdalina inhibited aldose reductase and sorbitol dehydrogenase in a noncompetitive, and mixed non-competitive manner, respectively. The V. amygdalina extract displayed potent inhibition of polyol pathway enzymes, and it needs to be determined if consumption affects the responses.